A customised standard to assess birthweight and fetal growth potential in Ireland. (16th November 2010) - Unterscheider, J; Geary, M; Daly, S; McAuliffe, F; Dornan, J; Morrison, JJ; Burke, J; Higgins, JR; Manning, F; Francis, A; Malone, F; Gardosi, J
Abstract : Objective: Fetal growth and birthweight is known to vary with maternal and pregnancy related physiological variables. The authors wanted to test this principle and derive a customised standard applicable for Ireland. Method: The cohort consisted of prospectively collected data in 2008/9 on Euroking maternity systems from five maternity units (Belfast, Coombe, Galway, Rotunda and Dublin), and included 11 973 case records with complete data and ultrasound dated pregnancies. The median birthweight in this cohort was 3460 g, at a median gestation of 279 days. Coefficients were derived by backward multiple regression. Results: Significant coefficients for physiological variables were derived for maternal height, weight, parity, sex of the baby and eight different ethnic groups living in Ireland. Pathological factors affecting term birthweight were pre-existing diabetes (+137 g), smoking (–225 g), pregnancy induced hypertension (–38 g) and maternal obesity (BMI≥30: –42 g). The expected birthweight at 40.0 weeks for a standard size, primiparous Irish mother in an uncomplicated pregnancy was 3489 g. Conclusion: Birthweight in our population is subject to similar factors to those observed in previous reports from UK, Australasia and USA. The derived coefficients can be used for customised assessment of fetal growth potential in Ireland.